1991
DOI: 10.1111/j.1365-2818.1991.tb03189.x
|View full text |Cite
|
Sign up to set email alerts
|

A preparation method of specimens of the fungus Penicillium chrysogenum for ultrastructural and immuno‐electron microscopical studies

Abstract: A combination of cryofixation without pre-treatment, freeze-substitution and lowtemperature embedding was used to prepare specimens of Penicillium chrysogenum for electron microscopy. To produce specimens which are thin enough for appropriate cryofixation, the P . chrysogenum colonies were grown between dissected-dialysis tubing on an agar plate, which in addition allowed longitudinal sectioning. In contrast to classical chemical fixation, this preparation procedure resulted in excellent preservation of ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Ultrathin HM20 sections of the yeast cells were mounted on nickel grids and incubated with affinity-purified anti-␤1,6-glucan polyclonal antibodies (1:300) (27). The antigen-antibody complex was visualized with secondary goat anti-rabbit antibodies (1:20) conjugated with 10-nm gold particles (Aurion, Wageningen, The Netherlands) (39). The labeled ultrathin sections were viewed in a Philips EM420 electron microscope, and micrographs were taken at an acceleration voltage of 80 kV.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrathin HM20 sections of the yeast cells were mounted on nickel grids and incubated with affinity-purified anti-␤1,6-glucan polyclonal antibodies (1:300) (27). The antigen-antibody complex was visualized with secondary goat anti-rabbit antibodies (1:20) conjugated with 10-nm gold particles (Aurion, Wageningen, The Netherlands) (39). The labeled ultrathin sections were viewed in a Philips EM420 electron microscope, and micrographs were taken at an acceleration voltage of 80 kV.…”
Section: Methodsmentioning
confidence: 99%
“…It can be seen that there were no significant changes due to the treatment. with and without using the fixative of fixative of Mfiller et al(1991b). Miiller et al(1991b).…”
Section: Resultsmentioning
confidence: 99%
“…In basidiomycetes, Hoch and Howard (1981) reported that the SPC and the dolipore septa may be changed in their morphology because of the aldehyde fixation. Müller et al (1991) documented a distortion of the plasma membrane in chemically fixed and freeze-fractured hyphal cells compared with cryofixed and freeze-fractured hyphal cells. Although the combination of cryofixation and freeze substitution may result in better preservation of the subcellular ultrastructure in hyphal cells, many serial sections must be made for final viewing of the topology of their organelles.…”
Section: Discussionmentioning
confidence: 98%
“…However, chemical fixation of hyphae may cause ultrastructural changes of organelles and subcellular structures in hyphae from similar structures in living hyphae (Hoch and Howard 1981, Howard and O'Donnell 1987, Müller et al 1991. In basidiomycetes, Hoch and Howard (1981) reported that the SPC and the dolipore septa may be changed in their morphology because of the aldehyde fixation.…”
Section: Discussionmentioning
confidence: 99%